2012
DOI: 10.1007/s12010-011-9525-3
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Expression and Tyrosine O-Sulfonation of Ax21 in Escherichia coli

Abstract: Ax21 (activator of Xa21-mediated immunity), a pathogen-associated molecular pattern secreted by Xanthomonas oryzae pv. oryzae, can be perceived by a membrane-located pattern recognition receptor Xa21 and triggered immune responses in rice. An Ax21-derived peptide (17-amino acid) containing a sulfated tyrosine-22 (axY(S)22) is sufficient for Ax21 activity. Here, we expressed Ax21 and O-sulfated its tyrosine-22 through coexpressing a putative tyrosine sulfotransferase, raxST, and two other genes involved in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Some of the retracted results have been reproduced in other laboratories (Shuguo et al, 2012; Wang et al, 2013). For example, Shuguo et al (2012) showed that a sulfated, 36-aa peptide, derived from the N-terminus of Ax21, can induce various defense responses in XA21-expressing rice such as accumulation of reactive oxygen species, mitogen-activated protein kinase activation and in planta XA21-mediated immunity.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Some of the retracted results have been reproduced in other laboratories (Shuguo et al, 2012; Wang et al, 2013). For example, Shuguo et al (2012) showed that a sulfated, 36-aa peptide, derived from the N-terminus of Ax21, can induce various defense responses in XA21-expressing rice such as accumulation of reactive oxygen species, mitogen-activated protein kinase activation and in planta XA21-mediated immunity.…”
Section: Introductionmentioning
confidence: 60%
“…For example, Shuguo et al (2012) showed that a sulfated, 36-aa peptide, derived from the N-terminus of Ax21, can induce various defense responses in XA21-expressing rice such as accumulation of reactive oxygen species, mitogen-activated protein kinase activation and in planta XA21-mediated immunity. Wang et al (2013) showed that ax21 deletion mutants in both Xoo (strain PXO99) and X. oryzae pv.…”
Section: Introductionmentioning
confidence: 99%
“…raxA and raxB are arranged in a putative operon (called raxSTAB ) together with the gene raxST , which is not a part of the TOSS (da Silva et al, 2004). Instead raxST is a sulfotransferase (Shuguo et al, 2012), which catalyze the transfer of sulfate from PAPS (3′-phosphoadenosine 5′-phosphosulfate) to a tyrosine residue. Sulfation of secreted peptides is often important for their biological function.…”
Section: Activator Of Xa21-mediated Immunity (Ax21)mentioning
confidence: 99%
“…DNA nucleotides coding for the polyhistidine affinity tag can also be created from synthetic oligonucleotides and cloned into an appropriate location in the desired plasmid. Alternatively, there are a wide variety of commercially available expression vectors for expression of polyhistidine-tagged recombinant proteins in different expression systems (Rabbani et al, 2010 andShuguo et al, 2012).…”
mentioning
confidence: 99%